2019
DOI: 10.1038/s41467-019-08347-2
|View full text |Cite
|
Sign up to set email alerts
|

Significant contribution of subseafloor microparticles to the global manganese budget

Abstract: Ferromanganese minerals are widely distributed in subseafloor sediments and on the seafloor in oceanic abyssal plains. Assessing their input, formation and preservation is important for understanding the global marine manganese cycle and associated trace elements. However, the extent of ferromanganese minerals buried in subseafloor sediments remains unclear. Here we show that abundant (108–109 particles cm−3) micrometer-scale ferromanganese mineral particles (Mn-microparticles) are found in the oxic pelagic cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…The absence of basal diffraction as well as small particle size, low crystallinity, and high Fe/Mn ratios indicate that our modern precipitates are hydrogenetic vernadite. A similar vernadite-like SAED pattern was reported in the micron-size Fe-Mn particles in deep-sea clay sediments 30 , which may have a common nature in depositional processes and environments.…”
Section: Installation Of Devices and Recoverysupporting
confidence: 78%
“…The absence of basal diffraction as well as small particle size, low crystallinity, and high Fe/Mn ratios indicate that our modern precipitates are hydrogenetic vernadite. A similar vernadite-like SAED pattern was reported in the micron-size Fe-Mn particles in deep-sea clay sediments 30 , which may have a common nature in depositional processes and environments.…”
Section: Installation Of Devices and Recoverysupporting
confidence: 78%
“…The 206 Pb/ 204 Pb values of the samples with positive IC1 scores are within the range of the Cenozoic seawater, and those with negative IC1 scores likely correspond to the terrigenous components (Table ). A recent study demonstrated that a significant amount of “micrometer‐scale Mn‐oxide particles” (much smaller than visible micronodules that are typically identified in pelagic clay; Figure S2 in the supporting information) are present in oxic pelagic clay in the South Pacific Ocean (Uramoto et al, ). Based on the features of Fe, Mn, Co, Ni, and Cu compositions, Uramoto et al () discussed that Mn microparticles are derived primarily from hydrogenetic precipitation from bottom water.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, REE sources may be related to Fe-rich authigenic (diagenetic) clay minerals and admixtures of allogenic components from continental areas [14,19,30]. The REE accumulation in pelagic sediments may also be related to external influx of Fe/Mn-microparticles [31]. The REE composition and distributional patterns may be also related to high temperature hydrothermal iron oxides and aluminosilicates, products of bedrock disintegration, or endogenous (volcanoes) and exogenous (desert dust) components [32].…”
Section: Ree In Deep-sea Sedimentsmentioning
confidence: 99%
“…In addition to these features, the seafloor is characterized by a regular bathymetric pattern that consists of a system of adjacent linear groups of ridges and valleys, aligned approximately perpendicular to the boundary between the Clarion and Clipperton Fracture Zones. Distances between neighboring crests vary from 1 to 10 km, with elevations above surrounding terrain up to hundreds of meters [31]. The CCFZ ocean crust is 10.6-10.8 km thick, and is composed of two complexes: (i) tholeiitic basalts, and (ii) overlying sediment cover, with a thickness of 100 to 300 m, and age range from Late Cretaceous to Quaternary [43,52].…”
Section: Geological Settingmentioning
confidence: 99%